Upaya Meningkatkan Hasil Belajar Siswa Materi Mari Mengaji dan Mengkaji Q.S. Al-Hujurat Ayat 13 melalui Model Problem Based Learning Kelas IV SDN 02 Sungai Beremas - Yosi Astaria; Ratih Afifania (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve student learning outcomes on the material Let's Study and Study Q.S. Al-Hujurat verse 13. Based on Cycle I, it can be seen that 18 students or 55% of students were declared to have completed their studies, while the rest were declared to have not completed their studies as many as 15 people or 45%. The results of these data, then for the Character of the Material Let's Study and Study Q.S. Al-Hujurat verse 13 in Phase B Class 4 SDN 02 Sungai Beremas the learning outcomes have not been completed classically because the students who have completed have not reached 80%. Based on Cycle II, it can be seen that 28 students or 87% of students were declared to have completed their studies, while the rest were declared to have not completed their studies as many as 5 people or 13%. The results of the data, then for class action, namely by applying the Problem Based Learning learning model in the subjects of Islamic Religious Education and Character Education, material Let's Study and Study Q.S. Al-Hujurat verse 13 at SDN 02 Sungai Beremas, class IV, the learning outcomes were completed classically.